2009
DOI: 10.1002/esp.1850
|View full text |Cite
|
Sign up to set email alerts
|

The role of the sediment budget in understanding debris flow susceptibility

Abstract: This study proposes a sediment-budget model to predict the temporal variation of debris volume stored in a debrisflow prone watershed. The sediment-budget is dominated by shallow landslides and debris outflow. The basin topography and the debris volume stored in the source area of the debris-flow prone watershed help evaluating its debris-flow susceptibility. The susceptibility model is applied to the Tungshih area of central western Taiwan. The importance of the debris volume in predicting debris-flow suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…3. Our results are consistent with those obtained by Dong et al (2009). Both severe rainfall and earthquakes would change the condition of RI, in terms of both the magnitude and number of debris flow events.…”
Section: Influence Of Rainfall Variation On Debris Flows Occurrencesupporting
confidence: 93%
See 1 more Smart Citation
“…3. Our results are consistent with those obtained by Dong et al (2009). Both severe rainfall and earthquakes would change the condition of RI, in terms of both the magnitude and number of debris flow events.…”
Section: Influence Of Rainfall Variation On Debris Flows Occurrencesupporting
confidence: 93%
“…The variation of critical RI is related to debris supply within the watershed. Dong et al (2009) developed a susceptibility index (SI) that accounted for debris supply to estimate the susceptibility to debris flow. They reported that the SI increased following the CCE and after TT (before the occurrence of debris flow), because the volume of debris contributed by shallow landslides increased; and that SI decreased when the volume of debris was reduced by debris outflow during TT and TMi.…”
Section: Influence Of Rainfall Variation On Debris Flows Occurrencementioning
confidence: 99%
“…Most of these models have been created using regional debris flow inventories derived from remotely sensed data. Statistical analyses, including logistic regression [12][13][14][15], discriminant analysis [16,17], and Bayes learning [18], are deemed to be suitable for susceptibility assessment in large and complex areas [19][20][21]. Using Bayes learning and logistic regression to predict debris flows in southwest Sichuan, China, Xu et al [22] pointed out that both methods have disadvantages: Bayes requires some variable assumptions that are difficult to be completely met in practice, whereas logistic regression needs large samples for the iterative calculation to obtain stable model parameters.…”
Section: Study Areamentioning
confidence: 99%
“…The impact of the Chi-Chi earthquake (Taiwan, 1999) on subsequent rainfall-induced debris flows has been studied by various authors (Lin et al 2006;Chen and Petley 2005). Dong et al (2009) used a discriminant model, which takes account of the debris budget, to study the influence of earthquakes on the subsequent occurrence of debris flows. Their study showed quantitatively that the occurrence of the 1999 Chi-Chi earthquake had significant impact on the debris flow occurrence during subsequent typhoons.…”
Section: Introductionmentioning
confidence: 99%